Rational design of agonists for bitter taste receptor TAS2R14: from modeling to bench and back - Di Pizio, Antonella; Waterloo, Lukas; Brox, Regine; Löber, Stefan; Weikert, Dorothée; Behrens, Maik; Gmeiner, Peter; Niv, Masha Y. (Cellular and Molecular Life Sciences, 2020)
Human bitter taste receptors (TAS2Rs) are a subfamily of 25 G protein-coupled receptors that mediate bitter taste perception. TAS2R14 is the most broadly tuned bitter taste receptor, recognizing a range of chemically diverse agonists with micromolar-range potency. The receptor is expressed in several extra-oral tissues and is suggested to have physiological roles related to innate immune responses, male fertility, and cancer. Higher potency ligands are needed to investigate TAS2R14 function and to modulate it for future clinical applications. Here, a structure-based modeling approach is described for the design of TAS2R14 agonists beginning from flufenamic acid, an approved non-steroidal anti-inflammatory analgesic that activates TAS2R14 at sub-micromolar concentrations. Structure-based molecular modeling was integrated with experimental data to design new TAS2R14 agonists. Subsequent chemical synthesis and in vitro profiling resulted in new TAS2R14 agonists with improved potency compared to the lead. The integrated approach provides a validated and refined structural model of ligand–TAS2R14 interactions and a general framework for structure-based discovery in the absence of closely related experimental structures.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Bioisosteric replacement; Bitter taste receptor; Drug design; GPCRs; Structure-based modeling